2016
DOI: 10.17795/iji-35094
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia as a Clinical Manifestation of Hepatitis C Among Patients With a Positive Anti-HCV Test

Abstract: Background: The hepatitis C virus (HCV) has been recognized as the cause of thrombocytopenia (defined as a platelet count of < 150,000 platelets/uL) occurring in patients with chronic hepatitis C. Thrombocytopenia occurs in 64% -76% of patients with cirrhosis and/or fibrosis, compared with 6% of non-cirrhotic patients with chronic liver disease. Objectives: The aim was to study the prevalence of thrombocytopenia in HCV patients without cirrhosis and splenomegaly. Patients and Methods: A cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…One of the most common abnormalities reported in patients with CHC is thrombocytopenia or low platelet count and the most commonly known causes include impaired production of platelets, increased platelet destruction or consumption, frequent bleeding, and infectious diseases, such as viral infection . Several studies reported that CHC infection is strongly correlated with thrombocytopenia, indicating that 64–76% of CHC infections, fibrosis, and cirrhosis showed manifestations of thrombocytopenia, compared with 6% of non‐cirrhotic patients . A powerful mechanism is the specific bind of HCV to platelet membrane CD81 receptor; therefore, production of autoantibody against this complex results in platelets phagocytosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common abnormalities reported in patients with CHC is thrombocytopenia or low platelet count and the most commonly known causes include impaired production of platelets, increased platelet destruction or consumption, frequent bleeding, and infectious diseases, such as viral infection . Several studies reported that CHC infection is strongly correlated with thrombocytopenia, indicating that 64–76% of CHC infections, fibrosis, and cirrhosis showed manifestations of thrombocytopenia, compared with 6% of non‐cirrhotic patients . A powerful mechanism is the specific bind of HCV to platelet membrane CD81 receptor; therefore, production of autoantibody against this complex results in platelets phagocytosis .…”
Section: Discussionmentioning
confidence: 99%
“…30 Several studies reported that CHC infection is strongly correlated with thrombocytopenia, indicating that 64-76% of CHC infections, fibrosis, and cirrhosis showed manifestations of thrombocytopenia, compared with 6% of non-cirrhotic patients. 31,32 A powerful mechanism is the specific bind of HCV to platelet membrane CD81 receptor; therefore, production of autoantibody against this complex results in platelets phagocytosis. 33 It might also occur in OCI.…”
Section: T He Current Study Comprehensively Evaluated the Prevalence mentioning
confidence: 99%
“…Findings of this study are higher than our study. In another study by Bano et al 14 13 found thrombocytopenia in 57.3% male patients. In same study most of the cases belonged to 5 th decade.…”
Section: Discussionmentioning
confidence: 86%
“…We have read, with great interest, the study conducted by Bano et al (1) in your journal. The aim of their study was to investigate the prevalence of thrombocytopenia in HCV patients without cirrhosis and splenomegaly.…”
Section: Dear Editormentioning
confidence: 99%